Developing Mobile Learning of Physics (MOBLEP) with android-based problem-based learning approach to improve students’ learning independence - Apit Fathurohman; Murniati Murniati; Sukemi Sukemi; Esti Susiloningsih; Erni Erni; Lintang Auliya Kurdiati; Samsuryadi Samsuryadi (Universitas PGRI Kanjuruhan Malang, 2023)
This development research aims to produce Mobile Learning of Physics (Moblep) by applying Android-based Problem Based Learning Approach to Increase Student Learning Independence which is valid and practical. The development model used is the Rowntree model modified with Tessmer's formative evaluation method. The tessmer's formative evaluation stages in this study include self-evaluation, expert review, one-to-one, and small group. At the expert review stage, data were collected through interviews, expert tests, and questionnaires using nine material experts, nine design experts, and eleven language experts. The one-to-one stage and the small group stage were carried out at SMA Negeri 1 Suak Tapeh. The results showed that the Mobile Learning of Physics (Moblep) with the Android-based Problem-Based Learning Approach that was developed, based on the results of the expert review, obtained a total percentage score of 94.73% from the validator and was included in the